A new modeling and evaluating method of the all stages of inherent energy consumption for the spindle system - Deng, Xiaolei; Wang, Xuanyi; Gao, Weiwei; Chen, Yahao; Ma, Honglie; Lin, Xiaoliang; Lin, Huan (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Against the backdrop of green transformation and energy efficiency improvement in the manufacturing industry, machine tools, as the core equipment of industrial production, have become a key element in reducing industrial carbon emissions through energy optimization. The spindle system, as the core component of a machine tool, accounts for 40%–60% of the total energy consumption during the cutting process. However, existing research mostly focuses on energy consumption during the cutting stage and lacks systematic modeling and quantitative evaluation of the inherent energy consumption characteristics for the spindle throughout the entire stage (standby, start-up, idle, and braking). This article proposes a modeling method that fills that gap. Using experimental data, we created energy consumption functions for each stage and established an evaluation system that included indicators such as standby power, expected idle power, and mass energy ratio. We conducted a validation study on the effectiveness of the model and the practicality of evaluation indicators for two vertical machining centers, VMC1165H and VMC855H. The results indicate that the research findings can provide a quantitative basis for optimizing machine tool design and energy-saving regulation of process parameters and help improve energy efficiency and low-carbon transformation in the manufacturing industry.